2022
DOI: 10.1108/rege-10-2021-0193
|View full text |Cite
|
Sign up to set email alerts
|

Women in mining: from subtle barriers to open prejudice

Abstract: PurposeThe core of this study is women in mining. The aim of this study was to analyze the perception of women, about their work environment, their career, the human resources policies and practices and the work–family balance in the context of a multinational organization in the sector.Design/methodology/approachThe case study was carried through semi-structured interviews with 27 women who work in this organization.FindingsAlthough women report that they are capable of exercising any position/function in the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 34 publications
1
1
0
1
Order By: Relevance
“…This implies that through mining, women in the study area has been able to contribute effectively toward the wellbeing of their family, and their career in general. The result is congruent with Bailey-Kruger (2012); NEITI (2020) ; Romano and Papastefanaki (2020); Ofosu, Torbor, and Sarpong (2022) and Valadares, De Carvalho Neto, Mota-Santos, and Diniz (2022).…”
Section: Tablesupporting
confidence: 84%
“…This implies that through mining, women in the study area has been able to contribute effectively toward the wellbeing of their family, and their career in general. The result is congruent with Bailey-Kruger (2012); NEITI (2020) ; Romano and Papastefanaki (2020); Ofosu, Torbor, and Sarpong (2022) and Valadares, De Carvalho Neto, Mota-Santos, and Diniz (2022).…”
Section: Tablesupporting
confidence: 84%
“…Women managers in the mining industry also experience harassment from their colleagues. This supports Botha's (2018) findings which are due to the small number of women in the mining industry, making them vulnerable to harassment (Botha, 2016;Botha, 2018;Kansake et al, 2021;Valadares et al, 2022). Companies are also seen as a challenge in the career development process.…”
Section: Research and Methodologysupporting
confidence: 74%
“…Female workers in the mining industry are vulnerable because there are fewer female workers than male workers (Valadares et al, 2022). The forms of challenges in the career development process are family, organizational and social challenges (Ismail & Ibrahim, 2008), which are caused by men playing more of a role as breadwinners, while women are considered to play the role of homemakers and looking after children, apart from having to deal with discrimination in the workplace, sexual harassment, and company policies that are not friendly to women/gender neutral policies (Powell, 1999;Powell & Graves, 2003;Verma, 2018).…”
Section: Career Development Of Women Managers In the Mining Industrymentioning
confidence: 99%
“…To be taken seriously, women must work harder than men and sacrifice their femininity (Phoshoko, 2022). This assertion is corroborated by Valadares et al (2022), who state that women must work much harder than men to demonstrate their competence in the workplace. Recent research conducted by the Intergovernmental Forum on Mining, Minerals, Metals and Sustainable Development (IGF) (2023) revealed that sexist biases in large-scale mining may be preventing women from entering the mining industry.…”
Section: Negative Gender Stereotypes and Workplace Culturementioning
confidence: 82%